2000
DOI: 10.1074/jbc.c000761200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of a Novel Scavenger Receptor for Oxidized Low Density Lipoprotein, SR-PSOX, on Macrophages

Abstract: Receptor-mediated endocytosis of oxidized low density lipoprotein (OxLDL) by macrophages has been implicated in foam cell transformation in the process of atherogenesis. Although several scavenger receptor molecules, including class A scavenger receptors and CD36, have been identified as OxLDL receptors on macrophages, additional molecules on macrophages may also be involved in the recognition of OxLDL. From a cDNA library of phorbol 12-myristate 13-acetate-stimulated THP-1 cells, we isolated a cDNA encoding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
276
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(280 citation statements)
references
References 21 publications
4
276
0
Order By: Relevance
“…CXCL16 is a novel transmembrane-type chemokine (8,9), which was also identified as a novel scavenger receptor for oxidized low density lipoprotein (13). In the present study, we have shown that immobilized CXCL16 is capable of inducing adhesion of plasma cells expressing CXCR6 without requiring G ␣i -mediated signaling or divalent cations (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…CXCL16 is a novel transmembrane-type chemokine (8,9), which was also identified as a novel scavenger receptor for oxidized low density lipoprotein (13). In the present study, we have shown that immobilized CXCL16 is capable of inducing adhesion of plasma cells expressing CXCR6 without requiring G ␣i -mediated signaling or divalent cations (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…Previous studies demonstrated the expression of CXCL16 on dendritic cells, macrophages, T cells, B cells, smooth muscle cells, and umbilical endothelial cells (4,5,(9)(10)(11). FLS from patients with RA are additional and new members of the group of cells producing CXCL16.…”
Section: Discussionmentioning
confidence: 98%
“…Membrane-bound, it serves as a scavenger receptor for phosphatidylserine and oxidised low-density lipoprotein [6], and facilitates the phagocytosis of bacteria [7]. Immunohistochemical analysis suggests that CXCL16 is expressed by lipid-laden macrophages in the intima of atherosclerotic plaques and by valvular and neocapillary endothelial cells in patients with infective endocarditis, suggesting a role in the pathogenesis of both diseases [8,9].…”
Section: Introductionmentioning
confidence: 99%